Pancasila Ideology in Practice: Ethnographic Study of Integration in Amaq Abir Theater West Nusa Tenggara - Rapi Renda; Mohamad Yudisa Putrajip; Galih Suryadmaja; I Wayan Kusuma Di Biagi; Daffa Satya Jaya Buana (Universitas Negeri Medan, 2025)
This study examines the integration of Pancasila values in the traditional theater performance of Amaq Abir, a cultural heritage preserved by Sanggar Pustaka Budaya in Central Lombok, West Nusa Tenggara. The urgency of this research arises from the impact of globalization, which often generates cultural dislocation, identity crises, and moral shifts. These conditions emphasize the importance of developing character education models grounded in local wisdom while reinforcing Pancasila as the nation’s ideological foundation. Using a qualitative design with an ethnographic approach, data were obtained through systematic observation, in-depth interviews, and documentation. The findings show that Amaq Abir performances embody the five principles of Pancasila through dialogic narratives, symbolic costumes, traditional music, and social interaction. Values of religiosity, humanity, unity, deliberation, and social justice are not only represented artistically but also lived communally by performers and audiences. The study positions Amaq Abir as more than folk entertainment; it serves as a medium for contextualized character education and ideological transmission. Its novelty lies in mapping how Pancasila values are integrated into traditional performance arts, framing them as cultural strategies and pedagogical tools. Broader implications highlight the revitalization of traditional arts, the strengthening of cultural identity, and the collaboration of local governments, educational institutions, and art communities to embed these practices into national character education agendas.